The Military Aleatory: Weaponizing Winds - Ryan Bishop (Media + Environment)
The conversion of dynamic systems from impediments to strategic advantages has long played a substantial role in the US military’s technological research and development. From signal interpretation with remote sensing systems to telecommunciations to algorithms, media and information theory, and the weather, the unintended consequences of both dynamic systems in nature and technological attempts to control them led to innovations and accidents, developments and prediction advances that furnish large swaths of our current global sensorial domain. The role of randomness within complex dynamic systems accounts for the opportunities and impediments these systems offer. A consistent logic of micro-slicing of dynamic environmental systems connects different historical periods of military weather interventions, a windowing procedure to find a signal in the noise, and possibly an advantageous one. An example of this can be found in a current military system for soldiers to model and predict low-atmosphere turbulence in the field. This article undertakes a brief examination of the role of nuclear technologies in relation to military meteorology, an overview of how control is found within the aleatory, followed by a section on military meteorology’s fundamental role in window modelling that reveal the logics and technics that detect signal from noise when none seems possible, before closing with military prediction of wind turbulence and a short cumulative refrain on wind and radiation exposure, with further links to the various sections.